Learning from vision-to-touch is different than learning from touch-to-vision - Wismeijer, Dagmar A.; Gegenfurtner, Karl R.; Drewing, Knut (Frontiers in Integrative Neuroscience, 2012)
We studied whether vision can teach touch to the same extent as touch seems to teach vision. In a 2 x 2 between-participants learning study, we artificially correlated visual gloss cues with haptic compliance cues. In two "natural" tasks, we tested whether visual gloss estimations have an influence on haptic estimations of softness and vice versa. In two "new" tasks, in which participants were either asked to haptically judge glossiness or to visually judge softness, we investigated how perceptual estimates transfer from one sense to the other. Our results showed that vision does not teach touch as efficient as touch seems to teach vision.